Feasibility Study of Audiovisual Learning Media in Case Method and Team-Based Project Models in Creative Writing Courses - Rosmawaty (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2024)
Feasibility presentation refers to how a teaching medium is packaged to have value and attractiveness based on the systematic sequence of presenting learning materials in the developed teaching media. This study aims to determine the feasibility of the audiovisual learning media that has been prepared. The method used is descriptive qualitative. The research results show that the developed teaching media received a positive response from subject matter experts regarding the feasibility of the presentation. The feasibility of this material presentation was obtained based on the validation results of a team of experts, including subject matter experts and design experts. Based on the validation results by a team of experts consisting of two subject matter experts and one instructional design expert, who are lecturers from the Faculty of Languages and Arts, The State University of Medan, the developed video teaching media falls under the "excellent" category with a validation result percentage of 96.78% in terms of content and "Good" with a rate of 87% in terms of media design. The next step in this development research series can be carried out based on these results.